Oral health knowledge and tooth loss among elderly relationships - Puspawati, Noerfarida; Mahirawatie, Ida Chairanna; Isnanto, Isnanto (Faculty of Dental Medicine Universitas Airlangga, 2025)
Background: Tooth loss is recognized as one of the major oral health challenges among the elderly. As people age, biological changes occur, including transformations in the oral tissue structure, commonly due to tooth loss. Poor oral health among the elderly is influenced by various factors, one of which is behaviour. Oral hygiene practices are closely linked to knowledge. The primary concern of this study is that most elderly patients attending the Prosthodontics Clinic at UNAIR Dental and Oral Hospital exhibit suboptimal dental function. Purpose: The objective of this study is to investigate the relationship between oral health knowledge and tooth loss in the elderly population. Methods: This study employed a cross-sectional design and involved 54 elderly individuals as respondents. Data were collected using a questionnaire to assess the respondents' level of dental health knowledge and a clinical assessment form to record tooth loss. The data were analyzed using the chi-square test to determine the association between elderly individuals’ knowledge of dental health and tooth loss at the Prosthodontics Specialty Clinic of UNAIR Dental and Oral Hospital in 2025. Results: The results showed that 42 elderly participants (77.8%) had a good level of dental health knowledge. However, 33 elderly participants (61.1%) had fewer than 20 functional teeth, indicating suboptimal dental function. A statistically significant association was found between dental health knowledge and tooth loss among the elderly, with a p-value of 0.043. Conclusion: Despite adequate oral health knowledge, tooth loss remains prevalent among the elderly, indicating the need for further research into additional contributing factors.